Desain Desain UI/UX Platform Berita Terintegrasi Menggunakan Metode Design Thinking: PENDAHULUAN - Akbar sholikhin; Ina Sholihah Widiati (Yayasan Nuraini Ibrahim Mandiri, 2024)
Advances in information technology have changed the way people access news. With the emergence of various news platforms that handle a variety of information, users are faced with the challenge of obtaining relevant information efficiently. The aim of this research is to design the user interface (UI) and user experience (UX) of a platform integrated news that provides easy access to various news sources on a website one website. This research uses a user- centered design approach to uncover user needs and preferences through a survey involving respondents from various backgrounds. The results of data analysis show the importance of effective search functions, categories clear news, and responsive design to improve user experience.The resulting prototype aims to reduce the complexity of accessing news, speed up the search process, and provide a more enjoyable experience for users.The proposed design not only pays attention to aesthetics but also ease of navigation, allowing users explore various news sources easily. This research is expected to contribute to the development of more user- friendly and efficient news platforms in today's digital era.